Understanding optimal cadence dynamics: a systematic analysis of the power-velocity relationship in track cyclists with increasing exercise intensity - Dunst, A. K.; Hesse, C.; Ueberschär, O. (Journal of Science and Cycling, 2024)
Background: The relationship between cadence and cycling performance is a critical yet complex aspect of sports science. This study investigates whether training zone programs should be adjusted to different cadences, addressing a gap in current understanding. Previous research has shown that cadence significantly influences metabolic responses across various exercise intensities, affecting blood lactate concentration, cardiac output, and respiratory measures (Michaelis & Müller 1942; Hess & Seusing, 1963; Eckermann & Millahn, 1967; Israel et al., 1967; Pugh, 1974; Gaesser & Brooks, 1975; McKay & Banister, 1976; Schürch et al., 1976; Seabrug et al., 1977; Löllgen et al., 1980; Hagberg et al., 1981; Böning et al., 1984; Chavarren & Calbet, 1999; Zoldaz et al., 2000; Foss & Hallén, 2004; Beneke et al., 2015; Beneke et al., 2018). Established parabolic functions describe the relationship between metabolic or cardiopulmonary states and cadence at specific work rates (Böning et al.; 1984; Zoldaz et al., 2000), revealing an inverted U-shaped relationship between power and velocity, even at submaximal intensities.